FRI0401 Safety of Resuming Tumor Necrosis Factor Inhibitors in Ankylosing Spondylitis Patients Concomitant with The Treatment of Active Tuberculosis: A Retrospective Nationwide Registry of The Korean Society of Spondyloarthritis Research. (15th July 2016) - Kim, H.W.; Lee, S.-H.; Baek, H.J.; Kim, T.-H.; Kim, Y.-G.
Abstract : Background: Patients who develop an active tuberculosis infection (TI) during tumor necrosis factor (TNF) inhibitor treatment typically discontinue TNF inhibitor and receive standard anti-tuberculosis treatment. However, there is currently insufficient information on patient outcomes following resumption of TNF inhibitor treatment during ongoing anti- tuberculosis treatment. Objectives: Our study designed to investigate the safety of resuming TNF inhibitors in ankylosing spondylitis (AS) patients who developed TI as a complication of the use of TNF inhibitors. Methods: Through the nationwide registry of the Korean Society of Spondyloarthritis Research, 3929 AS patients were recruited who were prescribed TNF inhibitors between June 2003 and June 2014 at fourteen referral hospitals. Clinical information about the patients who experienced TI after exposure to TNF inhibitors was analyzed. The clinical features of resumers and non-resumers of TNF inhibitor were compared and the outcome of TI was surveyed individually. Results: Fifty-six AS patients were treated for TI associated with TNF inhibitors. Among them, 23 patients resumed TNF inhibitors and these patients were found to be exposed to TNF inhibitors for a longer period of time and experienced more frequent disease flare up after discontinuation of TNF inhibitors compared with those who did not resume. Fifteen patients resumed TNF inhibitors during anti-tuberculosis treatment (early resumers) and 8 after completion of TI treatment (late resumers). Median time to resuming TNF inhibitor from TI was 3.3 and 9.0 months in the early and late resumers, respectively. TI was treated successfully in all resumers and did not relapse in any of them during follow-up (median 33.8 (IQR; 20.8–66.7) months). Conclusions: TI were treated successful in our AS patients, even when given concomitantly with TNF inhibitors. We suggest that early resuming TNF inhibitors in AS patients could be safe under effective coverage of the TI. Disclosure of Interest: None declared